Les problemes poses par l'approvisionnement en lait de l'Afrique tropicale - Tendances economiques. Produits laitiers - International Livestock Centre for Africa (1979)
Data on milk production, and consumption and import of dairy products in tropical Africa, w. ref. to development constraints of dairy industry, milk prices and development policies.